Co-creation as a catalyst to organizational change: exploring educators’ and designers’ perceptions during the design of new learning environments - Chavey, Michelle Ann Meyer (Kansas State University, 2021)
This qualitative research was designed as a participatory evaluative case study to explore the co-creation of new learning environments as a component of organizational change. It examines educators’ perceptions from a Midwestern suburban school district working with an architectural firm to design a new middle school. Research questions focused on: 1) The evaluation of a belief-based visioning effort during the co-creation of a new learning environment and 2) school district administrator views of how organizational change is impacted and implemented through co-creation and beyond. For the methodological approach, a case study was utilized and bounded by the early phases of an architectural design process – programming and schematic design – and involved the views of district-level administrators, building-level administrators, certified teachers, and architectural designers. Data for this study was collected through interviews, focus group discussions, documentation, and observation of the design process during co-creation meetings between the designers and the educators. Taking an iterative approach to data analysis, I moved through a series of cycles to consider angles from both the researcher and practitioner perspectives. A multistep coding process was used to understand common themes related to each research question with the connecting threads of co-creation woven through each and its implication on successful change. Findings showed the belief-based visioning tool had merit and was valuable to the educators who crafted the vision, as well as the designers who used the final learning-belief statements in the co-creation process. With additional time for reflection, collaboration, and discussion, the tool could be improved. Time continued to be a major element of this study, as the research revealed that the typical timeframe of the co-creation process to design new learning environments directly conflicts with what we know from literature about navigating organizational change in healthy ways. This revelation about time, co-creation and change has implications for designers and educators interested in implementing a co-creation process to provide physical environments for learning and a building culture that supports healthy change processes.
Keywords: Design; Co-creation; Change; Education; Educational leadership; Learning environments